FVC, FEV1 and FEV1/ FVC % in Rheumatoid Arthritic Female and their Relationships with Duration of the Disease - Yesmin, Farzana; Begum, Shelina; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2010)
Background: Rheumatoid Arthritis (RA) is the most common inflammatory disorder mediated through the immune system, affecting joints and various organs including lungs. Pulmonary dysfunction in RA patients has been reported. Objective: To observe FVC, FEV1 and FEV1/ FVC % in female patients of RA and their relationships with duration of the disease. Methods: This cross-sectional study was carried out in the Department of Physiology, BSMMU, Dhaka, from January to December 2009 on 90 RA female patients of 30-50 years age (Group B). For comparison, 30 age and BMI matched apparently healthy subjects (Group A) were also studied. According to the duration of disease, RA patients were subdivided into B1 (newly diagnosed), B2 (3-5 years ) and B3 (6-10 years ). They were selected from the Out Patient Department of Physical Medicine of Bangabandhu Sheikh Mujib Medical University, Dhaka. FVC, FEV1 and FEV1/FVC% of all the subjects were measured by a digital MicroDL spirometer. Results were expressed as percent of predicted value. For statistical analysis One-Way ANOVA, Unpaired Student's 't' test and Pearson's correlation coefficient test were performed, as required. Results: The mean percentage of predicted values of these lung function parameters in the healthy female subjects and newly diagnosed (B1) RA patients were within normal ranges. The mean percentage of predicted values of all the spirometric variables were significantly lower in the patients in B3 compared to those in B2 (FVC p<0.01, FEV1 p<0.01), B1 (FVC p<0.05, FEV1 p<0.05, FEV1/FVC% p< 0.001) and A (FVC p<0.01, FEV1 p<0.001, FEV1/FVC% p<0.001), except FEV1/FVC% in B3 vs B2 which was lower but nonsignificant. Again these same parameters were significantly lower in B2 in comparison to B1 (FVC p<0.001, FEV1 p<0.001, FEV1/FVC% p< 0.001) and A (FVC p<0.001, FEV1 p<0.05, FEV1/ FVC% p<0.001). In addition all the ventilatory variables had significant (p<0.001) negative correlation with durations of disease except FVC in B1, which was significant at p<0.01 level. Conclusion: This study reveals that pulmonary functions may be lower in patients of RA and the lung function is inversely related to the duration of disease. Key Words: FVC; FEV1; Rheumatoid Arthritis DOI: 10.3329/jbsp.v5i1.5412 J Bangladesh Soc Physiol. 2010 June; 5(1): 8-13